Navegando por territórios de formação docente permanente no ensino de geografia em Lages, Santa Catarina, Brasil: o local e o global em diálogo - Oliveira, Cristian Roberto Antunes de (My University, 2022)
This paper aims to analyze public policies between 2012 and 2021 on permanent training of geography teachers from the City Educational System of Lages, Santa Catarina, Brazil, and how they affect (or not) in their praxis. I highlight that I chose as a starting point for the theoretical scope to base my thesis on a metaphor. The metaphorical articulation between life and sailing is one of those common places in poetry that does not seem to wear out. My choice is based on a trip that takes as its cartographic path the permanent training of geography teachers, geography teaching in curricular public policies and pedagogical praxis. I believe it necessary to understand how public policies for Basic Education, which guide the training of geography teachers from the City Educational System of Lages, imply in the pedagogical teaching practice based on the praxis. The curricular policies are not neutral; they are pervaded by discourses, disputes, ideologies, political interests, and power relations. In the teaching of geography, that becomes even more evident through curriculum epistemological choices, as well as through the way teachers understand these guidelines, as allies in their practice (or not). I define my empirical basis supported by listening to teachers and training teachers, besides documental research and, finally, the use of the Geography Information System (GIS), which intertwines with the investigative object in the role I take as cartographer-researcher, being the cartographer responsible for the elaboration and confection of charts and maps. In the cartography of the thesis, I guide myself by the cardinal points, defined as the specific objectives: a) analyze the space of geography in public policies that guide the permanent training of teachers from the local to the global scope; b) investigate the results of new public policies in curriculum elaboration for geography teaching; c) describe how the moments of permanent training take place and are organized in the City Educational System of Lages, based on documents and geography teachers' perceptions; d) verify, based on the teachers? narratives, if the changes in public policies and the permanent training of geography teachers are articulated with their pedagogical practice. The ship that has accompanied us through the metaphor analysis bypasses the cooperation of the parts that comprise it, especially the one that commands it. I assume the need to position myself in face of the conducted study, conceiving the thesis that I defend based on the following meaning: curricular public policies for Basic Education, from local to global in dialogue, which guide the geography teacher permanent training in the City Educational System of Lages, Santa Catarina, Brazil, are correlated in a fragmented way with permanent training. Not all teachers have work conditions that favor the participation in training meetings, as well as there is a contradiction in the meaning assigned to the study meetings, as some dissociate the theories from the teaching practice, which implies in pedagogical practice and knowledge that is distant from the daily life of teacher training and training teachers, which reverberates little in the praxis. [resumo fornecido pelo autor]
Este trabalho tem como objetivo geral analisar as políticas públicas de 2012 a 2021 na formação permanente dos professores de Geografia do Sistema Municipal de Educação de Lages, Santa Catarina, Brasil e como implicam (ou não) em sua práxis. Ressalto que escolho como ponto de partida para o escopo teórico ancorar minha tese em uma metáfora. A articulação metafórica entre vida e navegação é um daqueles lugares-comuns da poesia que parece não sofrer desgaste. Minha opção se dá a partir de uma viagem, que escolhe como rota cartográfica a Formação Permanente de Professores de Geografia, Ensino de Geografia nas Políticas Públicas Curriculares e Práxis Pedagógica. Compreendo que seja necessário entender como as políticas públicas para a Educação Básica, que orientam a formação de professores de Geografia do Sistema Municipal de Educação de Lages, implicam no fazer pedagógico docente a partir da práxis. As políticas curriculares não são neutras, encontram-se permeadas por discursos, disputas, ideologias, interesses políticos e relações de poder. No ensino de Geografia isso se torna ainda mais evidente por meio das escolhas epistemológicas dos currículos, bem como pela forma como os docentes entendem essas orientações, como aliadas de sua prática (ou não). Defino minha base empírica amparado em escutar professores e professores formadores, além da pesquisa documental e, por fim, a utilização do Sistema de Informação Geográfica (SIG), que se entrelaça com o objeto investigativo no papel que assumo como cartógrafo pesquisador, sendo o cartógrafo responsável pela elaboração e confecção de cartas e mapas. Na cartografia da tese, oriento-me pelos pontos cardeais, definidos esses como os objetivos específicos: a) analisar o espaço da Geografia nas políticas públicas que orientam a formação permanente de professores, da esfera local à global; b) investigar quais os resultados de novas políticas públicas, na elaboração dos currículos do ensino de Geografia; c) descrever como são realizados e organizados os momentos de formação permanente no Sistema Municipal de Educação de Lages, a partir de documentos e percepções dos professores de Geografia; d) verificar, a partir das narrativas dos docentes, se as mudanças nas políticas públicas e a formação permanente dos professores de Geografia articulam-se ao seu fazer pedagógico. O navio que nos acompanha pela analogia da metáfora perpassa pela cooperação das partes que o compõem, sobretudo de quem as capitaneia. Assumo a necessidade de me posicionar diante da pesquisa realizada, concebendo a tese que defendo a partir da seguinte acepção: As políticas públicas curriculares para a Educação Básica, do local ao global em diálogo, que orientam a formação docente permanente em Geografia no Sistema Municipal de Educação de Lages, Santa Catarina, Brasil, estão correlacionadas de forma fragmentada com a educação permanente. Nem todos os professores têm condições de trabalho que favoreçam a participação nos encontros de formação, bem como há uma contradição no sentido atribuído aos encontros de estudos, pois alguns dissociam as teorias com a prática docente, o que implica em saberes e fazeres pedagógicos distantes do cotidiano de formação dos professores e professores formadores, o que pouco reverbera na práxis. [resumo fornecido pelo autor]
Keywords: Professores - Formação; Educação permanente; Educação - Lages (SC); Geografia - Estudo e ensino; Teachers - In-service training; Continuing education; Education - Lages (Brazil); Geography - Study and teaching